Numerička analiza frontalnog udara projektila 12,7 mm u pancirnu ploču - Pešić, Miloš S.; Živković, Aleksandra B.; Aničić, Aleksa D.; Blagojević, Lazar J.; Bonchev, Petko M.; Pantović, Predrag R. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The paper presents a numerical simulation of an impact of a 12.7 mm projectile on an armored metal plate with a velocity of 500 m/s at a distance of 900 m. Numerical simulations offer the possibility of drastically reducing the time required to obtain results in comparison to the time required for planning, organization and execution of experiments. The numerical simulation is done by variations in the thickness of the armor metal plate, specifically an armor metal plate of a thickness of 10 mm, 17 mm, 18 mm, and 23 mm. The mentioned armored plate thicknesses were chosen based on the results in order to determine the limit thickness of the armored plate for the projectile perforation limit, as well as for complete ballistic protection. Methods: Finite element modeling is used for analyzing stresses and deformations of the armored plates. The mentioned method calculates the impact of the projectile on the obstacle, precisely the collision of the projectile and the armor plate.Results: For the comparative analysis, the parameters used are the values of the stress and the displacement. For each of the above-mentioned thicknesses of the armored metal plate, the values of stress and displacement during projectile impact were determined. The results of this study show how the thickness of the armor plate affects the interaction of the projectile and the armor plate.Conclusion: If the physical and chemical characteristics of the armored plate remain unchanged, as the thickness of the armored plate increases, the possibility of projectile penetration decreases, and vice versa. This research is of essential importance because it analyzes the stresses and deformation of armor plates whose basic role is the protection of personnel and equipment from the projectile impact. In this regard, the thickness of the armored plate for semi-penetration of the projectile is determined.
Keywords: pancirna ploča; projektil; udar; metoda konačnih elemenata